Zar-i kāmil-i ʿiyār : tarjumah-i Miʿyār al-ašʿār - Ṭūsī, Naṣīr-ad-Dīn Muḥammad Ibn-Muḥammad aṭ- (Naval Kišor, 1903)
A sentence-by-sentence Urdu translation by Muẓaffar ʿAlī Asīr of a classic on Persian rhetoric by Naṣīr ad-Dīn Ṭūsī; includes excerpts from Mawlavī Saʿdallāh's marginal notes and Mahdī ʿAlī Zakī's commentary